Influence of different bioparticles on bed expansion characteristics of anaerobic fluidized bed reactors - Turan, M.; Ozturk, I. (Informa UK Limited, 2001)
Bed expansion characteristics and predicting biofilm development and biomass hold-up in the anaerobic fluidized bed reactor were investigated. The treatability studies of brewery wastes were carried out in a pilot-scale fluidized bed reactor for a nine months period. The expansion and particle mixing characteristics of a fluidized bed containing different bioparticles is a complicated function of many variables, including hydrodynamics, support characteristics, and biofilm structures. The biological fluidized bed reactors have two types of bed expansion; the first is due to an increase of the superficial velocity and the second is due to the microbial growth in the bed. A new relationship for the porosity of the biological fluidized beds, was developed. Biofilm thickness and bed porosity increased rapidly in the upper part of the bed and the bioparticles become lighter than the clean particles with decreasing effective density. Most bioparticles in the anaerobic fluidized bed reactor (AFBR) were ellipsoidal and the geometric mean diameters were considered as the characteristic diameter. Their surface roughness causes an increase in the drag force acting on the particle. Thus, the expansion coefficient increased from 3.44 to 3.64 as terminal settling velocity decreased from 6.99 to 4.29 cm/s. An almost linear relationship was observed between local porosity and biofilm thickness. The differences between the measured and calculated biomass concentrations varied in the range of 0.4 and 12% (average 4.6%) considering the results from the pilot-scale AFBR. The bed expansion rate of the AFBR, varied from 12.3 to 18.3% whereas, the expansion rate of the clean bed also found between 7.9 and 12.7%. Consequently, the bed expansion rate due to biofilm accumulation on the particles can be well described to vary between 4.4 and 5.6%.
Keywords: Beer; Industrial Waste; Models, Theoretical; Waste Disposal, Fluid; Bacteria, Anaerobic; Bioreactors; Biofilms; Biomass; Particle Size; Porosity